POTENSI KOMODITAS PERTANIAN KABUPATEN BOVEN DOGOEL PROVINSI PAPUA - Tahoba, Afia E; Wambrauw, Yustina Lina Dina (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2015)
Boven Digoel is one of Regencies in Papua Province. It is an new regencies that have high potency in agriculture so Analysis of Agricultural Potency is needed to develop this regency in the future. The methodology of this reserach is Location Quontient (LQ) with primary and secondary data. The result shows that The Potencial food crops are sweet potatoes and Cassava. In addition, Potencial Holtuculture Crops are spinach i Jair District and long beans in Mandobo District. Lastly, Potency in Plantation crops are bananas and rambutan in 14 districts and durian in 7 districts also rubber and alvocado in 6 districts aslso pineapple and salak in 4 districts.